Simultaneous quantification of anti-viral drugs Nirmatrelvir and Ritonavir used for the treatment of Covid-19 by HPLC method in bulk and dosage forms (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
In order to avoid possibly harmful side effects and providing clients with substandard goods, quality control is crucial. Therefore, it becomes vital to establish analytical procedures enabling the quality monitoring of commercial pharmaceutical products. In this present work, we had established, optimized, and evaluated a stability indicating approach for a co-packaged tablet containing Nirmatrelvir (NMTR) and Ritonavir (RTVR) using HPLC technology, in compliance with ICH criteria. Using a C18 symmetric, 5 µm (Silica column) stationary phase and 0.01M dibasic phosphate buffer (pH 3.0)/methanol (60:40) (v/v) as mobile phase, chromatographic separation of NMTR and RTVR was carried out at a solvent system flow pace of 1.0 mL/min, injection size of 10 μL, and column at an ambient temperature. With R2> 0.999, the NMTR and RTVR curves of calibration were a straight line from 37.50 to 225 μg/mL and 25.00 to 150 μg/mL, respectively. The detection and quantification limits for NMTR were 0.45 µg/mL and 1.363 µg/mL while for RVTR, it was 0.301 µg/mL and 0.912 µg/mL, respectively. Applying the standard addition approach, the recovery ranged from 98.819% to 99.877%; the precision for NMTR and RTVR was between 0.3256% and 0.5153 %RSD. Stress conditions including hydrolysis (acid, alkali and water), reduction, oxidation, photo degradation, as well as thermal stress were applied. Since the degradation products weren't hindering the NMTR and RTVR assay or detection, the approach may be characterized as stability indicating. The capacity of the suggested approach to separate NMTR and RTVR from their degradation products and excipients makes it suitable for utilization in stability studies as well as quality control assays of NMTR and RTVR in both their bulk and also dose forms (Paxlovid).